Pressure ulcer: Identification of grade and types.: Advanced healing unit of the Abel Gilbert Pontón Hospital (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
Bedsores, decubitus ulcer or pressure ulcer, are skin lesions, which can reach the subcutaneous cell or muscle caused by pressure, friction, prolonged friction, usually on a bony prominence. The most frequent sites of appearance are the surfaces that cover bony parts (bony prominence) such as the sacrum, trochanters, ankle, heels, etc. Its incidence varies between 7.5% in hospital units and 8.5% in patients treated at the first level of care, but 90% preventable. Most of the patients with this problem are elderly with or without neurological problems. A prospective case study was carried out, collecting information from the database of the nursing department on the fourth floor, advanced healing area of the Abel Gilbert Pontón Hospital. Regarding pressure ulcers or decubitus ulcers, we found that the most frequent was sacral location in 63% (422 patients out of a total of 666 patients) followed by heel ulcers in 18%; stage II being the most prevalent.
Keywords: eschar; pressure ulcer; incidence